HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PEMBERIAN SUSU FORMULA PADA BAYI 0-12 BULAN DI PUSKESMAS PAAL MERAH II KOTA JAMBI - Sulastri; Nurhasanah Zhafera; Silvia Mariana (LPPM STIKes Mitra Adiguna, 2026)
Infant formula is a type of milk specifically formulated to meet nutritional needs. Providing infant formula is a popular method of nutrition among parents (Lakshita, 2022). This study aims to understand the relationship between mothers' knowledge and attitudes regarding the provision of infant formula to infants aged 0–12 months at the Paal Merah II Community Health Center (Puskesmas) in Jambi City in 2026. This is a descriptive-analytic study with a cross-sectional design, conducted within the service area of ??the Paal Merah II Community Health Center, Jambi City, in 2026. The study population consisted of all infants at the Paal Merah II Community Health Center, totaling 155 infants. A random sampling technique using Slovin's formula was employed to select 34 respondents. The variables examined included knowledge and attitudes as independent variables, and the provision of infant formula to infants aged 0–12 months as the dependent variable. The results indicate that the majority of mothers (21 individuals or 61.8%) possessed a moderate level of knowledge. Most mothers (19 individuals or 55.9%) demonstrated a negative attitude, and 21 mothers (61.8%) provided infant formula to their babies. The study concludes that there is a significant relationship between knowledge regarding infant formula provision for infants aged 0–12 months at the Paal Merah II Community Health Center (p-value = 0.04; p < 0.05), and a significant relationship between attitudes regarding infant formula provision for infants aged 0–12 months at the same center (p-value = 0.03; p < 0.05).